Rules of fracture propagation of hydraulic fracturing in radial well based on XFEM - Xiaolong Li; Wen Xiao; Zhanqing Qu; Tiankui Guo; Jianxiong Li; Wei Zhang; Yu Tian (Journal of Petroleum Exploration and Production Technology, 2018)
Abstract The radial well fracturing has been applied and achieved effective output. However, the fracture morphology and propagation law of it are still remain unclear, which limits the development and application of it. A 3D numerical model is established by ABAQUS to solve the current problems. The stage of fracture propagation is simulated by the extended finite element method. The conclusions stated that in situ stress field distribution was changed during the radial well fracturing and the induced stress field along the radial well is established at the same time. The propagation of major fracture is orientated by the induced stress in a certain area. The guiding function of fracture orientated propagation is evaluated by included angle η between the axis of radial well and equivalent fracture. The smaller the value of η is, the better effect of fracture orientated propagation is. The increase of horizontal stress difference and decrease of vertical density of radial wells are unfavorable to decrease the value of η. The failure pressure grows up with the azimuth angle of radial well increasing. The increasing of elastic modulus of formation is not conducive to the effect of radial well fracturing. The increasing of Poisson’s ratio of formation is conducive to the failure pressure and maximum fracture width, but not as helpful as to decrease the value of η. Larger diameter of radial well is better for fracture oriented propagation. Operation parameters of fracturing fluid viscosity and construction displacement have less effect on the value of η. Also, the degree of different parameters influence on value of η, failure pressure and maximum fracture width is ranked by the grey correlation method. The results can be referred to prediction of fracture propagation and design of radial well completion or fracturing.